Acute gastrointestinal injury in critically ill patients with COVID-19 in Wuhan, China - Sun, Jia-Kui (World J Gastroenterol, 2020)
BACKGROUND: The coronavirus disease 2019 (COVID-19) is spreading rapidly around the world. Most critically ill patients have organ injury, including acute respiratory distress syndrome, acute kidney injury, cardiac injury, or liver dysfunction. However, few studies on acute gastrointestinal injury (AGI) have been reported in critically ill patients with COVID-19. AIM: To investigate the prevalence and outcomes of AGI in critically ill patients with COVID-19. METHODS: In this retrospective study, demographic data, laboratory parameters, AGI grades, clinical severity and outcomes were collected. The primary endpoints were AGI incidence and 28-d mortality. RESULTS: From February 10 to March 10 2020, 83 critically ill patients out of 1314 patients with COVID-19 were enrolled. Seventy-two (86.7%) patients had AGI during hospital stay, of these patients, 30 had AGI grade I, 35 had AGI grade II, 5 had AGI grade III, and 2 had AGI grade IV. The incidence of AGI grade II and above was 50.6%. Forty (48.2%) patients died within 28 days of admission. Multiple organ dysfunction syndrome developed in 58 (69.9%) patients, and septic shock in 16 (19.3%) patients. Patients with worse AGI grades had worse clinical variables, a higher incidence of septic shock and 28-d mortality. Sequential organ failure assessment (SOFA) scores (95%CI: 1.374-2.860; P < 0.001), white blood cell (WBC) counts (95%CI: 1.037-1.379; P = 0.014), and duration of mechanical ventilation (MV) (95%CI: 1.020-1.340; P = 0.025) were risk factors for the development of AGI grade II and above. CONCLUSION: The incidence of AGI was 86.7%, and hospital mortality was 48.2% in critically ill patients with COVID-19. SOFA scores, WBC counts, and duration of MV were risk factors for the development of AGI grade II and above. Patients with worse AGI grades had a higher incidence of septic shock and 28-d mortality.